Investigation of the Relation Between Intraarticular Bleedings and Symptom Severity of Attention Deficit Hyperactivity Disorder in Children and Adolescents with Haemophilia (Annals of Medical Research, 2021)
Aim: Intra-articular bleedings in haemophilia patients and movement restrictions and joint deformities that occur as a result of these bleedings constitute an important health problem and deteriorate the quality of life for children. The purpose of this study is to investigate the relation between intra-articular bleedings and symptom severity of attention deficit hyperactivity disorder and disruptive behavior disorders in children and adolescents with haemophilia.
Keywords: Hemophilia; Attention Deficit And Hyperactivity Disorder; Intraarticular Bleeding.